Characteristics of perineal pain postpartum in women - Medina Piedrahita, Paula Andrea; Borrero Cortés, Crystian; Herrera Gómez, Pedro José; Ospina Díaz, Juan Manuel (Universidad y Salud, 2016)
Introduction: Postpartum perineum pain is a common clinical problem, which is not addressed in detail in Colombia. Objective: To assess prevalence, magnitude and possible factors associated with postpartum perineum pain in a sample of women in the Hospital “La Victoria-Instituto Materno Infantil”, in Bogotá. Materials and methods: A prospective observational study was performed where the degree of perineum pain perceived by 133 postpartum patients was evaluated by using numerical analog scale of pain when they were sitting down, lying, walking and going to the bathroom (urination and/or defecation), at 12 and 48 hours of postpartum . Demographic, birth and newborn data were taken directly from the medical records. Results: Overall prevalence of moderate to severe perineum pain 36 to 39.5% depending on the activity at 12 hours of delivery, and since 28 to 31.6% at 48 hours after it. Perineum pain was associated, during any of the activities assessed, with the use of epidural analgesia during labor, laceration of degree II or greater, birth weight and head circumference of the newborn. Better analgesic effect of acetaminophen doses as 3 g per day or more was registered. Conclusions: Moderate to severe perineum pain affects less than 50 % of women with vaginal postpartum. It is associated with the frequency and degree of perineum trauma. The results suggest the need for further study of the most appropriate analgesic doses for these patients.